Fundamental aspects of isovolumetric contractility measurements of urinary bladder - WA Van Duyl (Archive of Urological Research - Peertechz Publications, 2021)
In 2004 Griffiths published: "Detrusor Contractility: Order Out of Chaos" [1]. It was a critical assessment of the many competing ways of assessing detrusor contractility in the urodynamic clinic. Different isovolumetric methods and pressure flow studies were considered.